Biocompatible neem gum-modified polyvinyl alcohol composite as dielectric material for flexible energy devices - Kiruthika, Parangusan (2024)
In our pursuit of a flexible energy storage solution, we have developed biocompatible (bc)-NG/PVA composite polymers by combining neem tree gum (NG) with polyvinyl alcohol (PVA). This innovative bio-inspired approach harnesses NG's unique properties for both the bio-electrolyte and bio-electrode components. The resulting bc-NG/PVA composites exhibit superior dielectric strength and versatility, surpassing traditional inorganic ceramic dielectrics in advanced electronics and pulsed power systems. Our study investigates the dielectric characteristics, conductivities, electric modulus, and impedance parameters of Pure PVA and NG-doped PVA composites. Adding 5 % NG to PVA significantly boosts its conductivity from 10−8 S cm−1 to 10−4 S cm−1, while the dielectric constant of PVA/5 % NG composite jumps to 104.5 compared to pure PVA. These improvements position the composite films of 5 % NG added PVA as promising materials for diverse applications. The heightened performance of these NG-blended PVA composite materials underscores their potential as a valuable resource for flexible energy storage solutions.